Bodily practices / physical activity in five years of Telehealth Goias, Brazil - Pessoni, Alana; Nascimento, Wedson Guimarães [UNESP]; Pasquim, Heitor (FapUNIFESP (SciELO), 2022)
Telemedicine is a supporting tool for the continuing education of Brazil’s Unified Health System (SUS) network health workers. Bodily practices/physical activity are relevant topics to be addressed in such an environment as health-promotion actions. This study aimed to analyze the content of bodily practices and physical activity through the medical records of teleconsultations and video classes of the Telehealth Center of Goias, Brazil. This qualitative, exploratory research analyzed medical records and video classes from a Collective Health theoretical perspective. As a result, 180 medical records and 23 video classes targeting bodily practices/physical activity content were identified. The analysis evidenced teleconsultations more frequently related to physical training, which aimed to prevent and control NCDs, and the effort by teleconsultants to present different elements of body culture and the expanded clinic, in accordance with the National Health Promotion Policy.
Práticas corporais / atividades físicas em cinco anos de Telessaúde Goiás
Keywords: Collective Health; Physical Activity; Primary Health Care; ⃡ Telehealth